EFFECTIVENESS OF PRE-OPERATIVE NURSING INTERVENTION PROGRAM ON ANXIETY AND PERCEIVED CONTROL PROGRAM IN PATIENT UNDERGOING CARDIAC SURGERY - YASIN, M; ARSHAD, M; NIGAR, Z; TASNEEM, SS; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Patients undergoing cardiac surgery often experience significant preoperative anxiety, which can adversely affect surgical outcomes and recovery. Enhancing perceived control through structured nursing interventions has shown potential in alleviating anxiety and improving patient outcomes. However, evidence on the effectiveness of such interventions in resource-limited settings, such as Pakistan, is limited. Objective: To evaluate the effectiveness of a preoperative nursing intervention program in reducing anxiety and enhancing perceived control among patients undergoing cardiac surgery. Methods: This randomized controlled trial included 56 adult patients scheduled for cardiac surgery at Social Security Hospital, Lahore. Participants were randomly assigned to either an intervention group, receiving a structured nursing program, or a control group, receiving standard care. The intervention included educational sessions, relaxation techniques, and personalized consultations. Anxiety and perceived control were measured pre- and post-intervention using the State-Trait Anxiety Inventory (STAI) and a validated perceived control scale. Statistical analyses were conducted using paired and independent t-tests. Results: The intervention group demonstrated a significant reduction in mean anxiety scores (from 47.2 to 38.3, p < 0.001) and an improvement in mean perceived control scores (from 22.4 to 26.8, p < 0.01). Participant feedback indicated high satisfaction, with 78.6% expressing moderate to high approval of the program. Conclusion: The preoperative nursing intervention program effectively reduces anxiety and enhances perceived control in patients undergoing cardiac surgery. Integrating such interventions into standard care can improve psychological well-being and surgical outcomes, particularly in resource-limited healthcare settings. Further research is recommended to evaluate the long-term benefits and applicability of these interventions in diverse populations.